2018
DOI: 10.1515/folmed-2017-0083
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the External Branch of the Superior Laryngeal Nerve during Thyroid Surgery

Abstract: Of all 102 thyroid procedures 87 (85.3%) patients underwent total thyroidectomy and 15 (14.7%) had unilateral thyroid lobectomy. One hundred fifty-five (82.01%) out of 189 expected EBSLN were identified and investigated intraoperatively when trying to identify visually EBSLN by the so called classical (conventional) methods of prevention. With the use of IONM, 181 (96.76%) EBSLN were correctly identified. Compared to the preliminary results of visual identification - 155/189 (82.01%) EBSLN, the degree of ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Friedman et al [17] reported an EBSLN visualization rate of 85.1%, and they found that the remaining branches run deep into the inferior constrictor muscle fibers. Recent studies have reported that the EBSLN can be visually identified in up to 93% of thyroidectomy cases [131819202122]. Despite anatomical integrity, adequate motor function of the nerve branch may not always be confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Friedman et al [17] reported an EBSLN visualization rate of 85.1%, and they found that the remaining branches run deep into the inferior constrictor muscle fibers. Recent studies have reported that the EBSLN can be visually identified in up to 93% of thyroidectomy cases [131819202122]. Despite anatomical integrity, adequate motor function of the nerve branch may not always be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, on the basis of our results in primary thyroid surgery, functional identification rates of the EBSLN could exceed 95% due to appropriate anatomical dissection and proper use of electrophysiological monitoring. Previous studies have reported the successful identification of the EBSLN with the assistance of IONM [118192021222627]. After significant advances and improvements in anatomical knowledge, surgical technique, and electrophysiological monitoring, the EBSLN identification rate has been reported to reach more than 90% in recent studies [34222328].…”
Section: Discussionmentioning
confidence: 99%
“…Employing IONM routinely would allow identification of these unexpected circumstances. This ability to identify motor nerves also applies to improving EBSLN identification rates from 79.1% to 97.5% …”
Section: Discussionmentioning
confidence: 94%
“…Before the end of the operation, while anatomical integrity is confirmed, neural monitoring is required to exclude the elimination of thermal damage and strain injury and verify neural function. Electrostimulation causes simultaneous contraction of the cricothyroid muscle in both the straight and oblique abdomen as the standard of neurological integrity (3,14,29). Nevertheless, IONM does not completely eliminate the risk of nerve injury caused by unintentional injuries (30,31), and the surgeon's experience and full understanding of anatomy and possible variations are more important than the aid of high-tech instruments during thyroid surgery (32).…”
Section: Discussionmentioning
confidence: 99%
“…Before the end of the operation, while anatomical integrity is confirmed, neural monitoring is required to exclude the elimination of thermal damage and strain injury and verify neural function. Electrostimulation causes simultaneous contraction of the cricothyroid muscle in both the straight and oblique abdomen as the standard of neurological integrity ( 3 , 14 , 29 ).…”
Section: Discussionmentioning
confidence: 99%